Seismic Performance Evaluation of Double-Skin Semi-Base-Isolated Building Using Incremental Dynamic Analysis - Mohammad Parsaeimaram; Congqi Fang; Xianqi Luo; Chandan Shakya (Advances in Civil Engineering)
Base isolation is a widely accepted earthquake damage prevention technique. This method decouples the superstructure from the base by putting a flexible layer under each column, thereby elongating the time period of structures. Semi-base isolation (SBI) in double-skin structures is an effective technique to reduce the dynamic responses of structures due to earthquake motions, by utilizing the isolation devices in part of it instead of the entire base. This study presents a double-skin structure consisting of outer fixed base frames with shear walls that have been detached from the inner core with a minor gap. The inner core of the structure has been dissociated from the base using the elastomeric bearings. Seismic response of 10-story double-skin structure with inner isolated core was compared to that of inner fixed base core to consider the yielding and collapse probability of the structure using the incremental dynamic analyses (IDA). The results showed that the time period in SBI buildings can be adjusted with the use of coupling beams between the inner and outer frames. Also, the time period and interstory drift ratio are both reduced as more floors are given coupling beams. However, these coupling beams are the most effective at the topmost floors.